2010
DOI: 10.1021/jp910799a
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior of Transparent Film Heaters Made of Single-Walled Carbon Nanotubes

Abstract: We investigate thermal behavior of transparent film heaters (TFH) made of single-walled carbon nanotubes. We fabricate the TFH by using the spray coating method. We studied the temperature dependence of the electrical resistance of the TFH in terms of Joule and external heating in various gas environments. Test results show that the effect of the electrical current through the TFH on the temperature dependence of the electrical resistance is not important and that the humidity and the degree of vacuum signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 24 publications
0
42
0
1
Order By: Relevance
“…[4][5][6] Currently, tin-doped indium oxide (ITO) lms are typically used for this purpose due to their suitable optoelectronic properties; 1,2,4-6 however, ITO-based lm heaters are limited by a slow thermal response time, high brittleness on exible substrates, poor thermal stability and the increasing price of ITO. 1,6,9,11 More recently, metal-based transparent heaters based on random networks of metallic nanowires or metal mesh lms have emerged as the most promising alternative material to ITO lms by virtue of their fast thermal response and low sheet resistance. A suitable replacement using carbon-based nanomaterials such as graphene and nanotubes has been extensively studied to address the limitations of ITO lm heaters over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Currently, tin-doped indium oxide (ITO) lms are typically used for this purpose due to their suitable optoelectronic properties; 1,2,4-6 however, ITO-based lm heaters are limited by a slow thermal response time, high brittleness on exible substrates, poor thermal stability and the increasing price of ITO. 1,6,9,11 More recently, metal-based transparent heaters based on random networks of metallic nanowires or metal mesh lms have emerged as the most promising alternative material to ITO lms by virtue of their fast thermal response and low sheet resistance. A suitable replacement using carbon-based nanomaterials such as graphene and nanotubes has been extensively studied to address the limitations of ITO lm heaters over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent and conductive films have covered the research fields of material science and engineering, capable of fulfilling requirements in various applications, such as light-emitting diode (LED) [1], organic solar cell [2], supercapacitor [3,4], nanogenerator [5,6], capacitive strain sensors [7], liquid crystal display (LCD) [8], heater [9][10][11], transistor [12,13], electromagnetic interference (EMI) shielding [14], charge-trap memory [15], and loudspeaker [16]. The traditional and commercial material for high transparent and conductive films is indium tin oxide (ITO).…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] A previous study reported that the MWCNT sheets could be used as a transparent heater on a glass substrate. Moreover, the measured steadystate temperatures were relatively low compared to others 25,35 and should be tested on polymer substrates for flexible applications, such as curved windows. However, despite the successful demonstration of the MWCNT sheet heaters, the fundamental heat transfer mechanism is not completely understood due to the complex phenomenon of heat dissipation.…”
Section: Introductionmentioning
confidence: 89%
“…The most common method for ITO deposition is vacuum sputtering. Kim et al 25 investigated the thermal behavior of transparent film heaters made from SWCNT as well, but a spray coating method was selected for fabricating the heater. Furthermore, an ITO film is fragile, which means that it is damaged easily when subjected to mechanical bending deformation.…”
Section: Introductionmentioning
confidence: 99%